Analisis Faktor yang Mempengaruhi Tingkat Kepuasan Pelayanan Kantor Balai Desa Medang Deras Batubara - Batubara, Rizki Wulanita; Purba, Rakhmawati; Siahaan, Rumiris; Harahap, Hastuty Handayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the factors that influence the level of service satisfaction at the Medang Deras Village Hall office, Batubara Regency. Using a Quantitative Descriptive type of research with a sample of 96 respondents who are residents of Medang Deras Village. Data was processed using SPSS (Statistical Product and Service Solution) version 25.00. From this research it can be concluded that facilities influence community satisfaction. Village Official Behavior Variables have no effect on Services. Administration influences the Community Satisfaction Variable. The dominant influence on the level of service satisfaction is the administrative variable